Hubungan Pengetahuan Mengenai Hidrasi Sehat dan Kecukupan Minum Air Putih dengan Kelebihan Berat Badan: Tinjauan Pustaka - Muhammad Abdul Ghoni Sutardi; Angraini, Dian Isti; Zuraida, Reni (CV. Jasa Sukses Abadi, 2023)
Water is a very important nutrient and is the most constituent component of the human body. Most of the water required by the body comes from drinking. Each person's fluid needs vary depending on physical activity, age, weight, ambient temperature and humidity. Fluid water is recommended over other types of beverages. Water needs about two liters or eight glasses a day for adolescents and adults who do light activities in the office and home under daily temperature conditions. Hydration knowledge can be a factor that affects the fulfillment of a person's water intake. Good hydration knowledge will make a person choose fluid consumption based on quality and quantity so that their fluid needs are met. Unfulfilled fluid intake can lead to dehydration. Dehydration is defined as a state of the body when fluid expenditure is greater than fluid intake. Dehydration can be a risk factor for overweight. Overweight is a condition when there is an accumulation of excess fat due to an imbalance between energy intake and energy used for a long time. Dehydration can cause a decrease in cognitive function and mood that causes weakness and laziness in physical activity; dehydration also causes fluid and electrolyte imbalances that increase appetite; and dehydration can increase glycerol and free fatty acids resulting in increased triglyceride formation. Adequate water intake can lead to weight loss by slowing gastric emptying and increasing metabolism.